Universities in capacity building in sustainable development: focus on solid waste management and technology - Agamuthu, Pariatamby; Hansen, J.A. (2007)
This paper analyses some of the higher education and research capacity building experiences gained from 1998-2006 by Danish and Malaysian universities. The focus is on waste management, directly relating to both the environmental and socio-economic dimensions Of Sustainable development. Primary benefits, available as an educational legacy to universities, were obtained in terms of new and enhanced study curricula established on Problem-oriented Project-based Learning (POPBL) pedagogy, which strengthened academic environmental programmes at Malaysian and Danish universities. It involved more direct and Mutually beneficial cooperation between academia and businesses in both countries. This kind of university reach-out is considered vital to development in all countries actively striving for global and sustainable development. Supplementary benefits were accrued for those involved directly in activities such as the 4 months of field studies, workshops, field courses and joint research projects. For students and academics, the gains have been new international dimensions in university curricula, enhanced career development and research collaboration based on real-world cases. It is suggested that the area of solid waste management offers opportunities for much needed capacity building in higher education and research, contributing to sustainable waste management on a global scale. Universities should be more actively involved in such educational, research and innovation programmes to make the necessary progress. ISWA can Support capacity building activities by utilizing its resources - providing a lively platform for debate, securing dissemination of new knowledge, and furthering international networking beyond that which universities already do by themselves. A special challenge to ISWA may be to improve national and international professional networks between academia and business, thereby making education, research and innovation the key driving mechanisms in sustainable development in solid waste management.